Exploring the intersections of immigrant seniors’ digital literacies and social connectedness: a Canadian study - Lin, Ching-Chiu; Li, Nathan J.; Lee, Ena (Frontiers in Education, 2023)
Seniors’ adoption of emerging technologies is crucial to their social connectedness, well-being, and digital participation in society. This article presents a Canadian study on how immigrant seniors established and sustained social connections through their engagement with digital technologies during the COVID-19 pandemic. Specifically, we aim to (1) deepen understandings of how immigrant seniors’ learning through and about technologies can shed light on our conceptualization of seniors’ digital literacies and (2) suggest programs and pedagogies that could foster lifelong learning for seniors. Data were collected through interviews, observations, and digital artifacts from a sample of immigrant seniors (N:16). Through narrative, we stitch together the personal and sociocultural perspectives from four seniors’ stories for holistic insights into their learning and engagement with technologies. Their stories also emphasize possibilities for dynamic and interconnected digital engagement and the inseparable link between community support and developing seniors’ digital literacy. Social interaction plays a pivotal role in facilitating, fostering, promoting, and enhancing seniors’ digital literacies. Our findings challenge preconceived notions about how seniors navigate digital technologies and offer strategies for supporting community service agencies in designing and implementing senior-friendly digital literacy programs.